LEED-CI V3 and V4 Silver and Gold Projects in China and the U.S. - Svetlana Pushkar (Applied Sciences, 2020)
Leadership in Energy and Environmental Design Commercial Interiors (LEED-CI) versions 4 (v4) and 3 (v3) Silver and Gold projects have been widely used in both the U.S. and China. This study aimed to compare the LEED-CI-Silver and LEED-CI-Gold v3 and v4 in China and the U.S. The design of the study comprised two stages: (1) to identify all LEED-CIv4 projects in China and the U.S. at the Silver and Gold levels for 2014–2019; and (2) to collect the same number of LEED-CIv3 projects for each certification level from the same cities of China and from the same states of the U.S. at the same times, if possible. Cliff’s δ or the log odds ratio effect size was used to evaluate the difference between the achieved and the possible points, and the difference between the Silver and Gold projects in China and the U.S. The results show that, in the Silver-to-Gold transition, in China, the water–energy–site–human health saving strategy was used, while in the U.S., only the water–energy saving strategy was used.